Effect of livestock-crop integration on grazing time of cattle in a subhumid African savanna - Bayer, W.; Otchere, E.O. (Australian Academy of Science, 1985)
In the Nigerian subhumid savanna studies of grazing behaviour by herded cattle reveal utilisation of wide range of feed resources including browse, crop residues and recent fallow, all of which are more nutritious than natural range. A comparison of grazing in a farming area and in a grazing reverse shows greater use of crop residues in the former and greater use of browse in the latter. In both areas the short grazing time compared with that of free-ranging animals may limit feed intake and contribute to low cattle productivity. On account of labour competition between herding and cropping and the need for tight herd control, grazing time in the growing season is restricted to only 5 h per day. Thus close spatial and operational integration of herding and cropping by agropastoralists appears to give easier access to crop residues in the dry season and fallows in the wet, thus partly compensating for the shortest grazing day.